Analysis of Receivable Management in Auto Industry with reference to Pune Region (International Journal of Food and Nutritional Sciences, 2019)
The Indian economy began to take off with the expansion of the automobile sector. For many businesses, a sizable amount of their current assets are receivables. Essentially, the largest portion of current assets, following inventories, are trade debtors. They make up roughly one-third of India's current assets. Credit-granting and debt-creation are equivalent to the company's funds being blocked. It should be mentioned that credit sales are the only way to maximize sales. Increased credit sales activity increases the risk that funds will be blocked as receivables in total current assets. As a result, managing accounts receivable in the automotive industry is extremely difficult. The data from the automobile industry was used to conduct the current study.